The Effectiveness of Support Group Program in Improving Self -Efficacy among Diabetic Support Group Members in Saudi Arabia - Saeed Belobaied, Shroog; Al-dehaim, Lolwah Abdurrahman; alfrijat, Asmaa; AlHarbi, Moahammed Saadi (KHD-Production, 2024)
Diabetes mellitus is one of the most prevalent chronic diseases that affect most of the population all over the world, this disease has many defective impacts on people's health self-confidence, and efficacy, so, establishing some supportive and educative programs to enhance diabetic patients' self-sufficiency is mandatory to give some of the positive impact on patients' health and self-esteem. This study aims to measure the self-efficacy level among Support group members diagnosed with type 2 diabetes in Saudi Arabia. Using an experimental study design on a group of diabetic patients to measure their self-efficacy level by conducting a pre- and post-questionnaire and recording their responses then analyzing them using Chi-square and paired t-test statistical programs. Findings showed that diabetes patients' perceptions of their abilities to manage their condition improved significantly after participation in the support group. Statistical analysis revealed that the experimental group's confidence in their capacity to manage their diabetes was much higher than the control group's. The study found that out of 370 diabetic patients (male and female) ranging in age from 30 to 50 years old, there is a statistically significant difference (≤ 0.05 α) in the confidence level in managing the disease and the level of self-sufficiency development favoring the last group. It was noted that performing the support group to raise the diabetic patients' efficacy to deal with diabetes mellitus effectively is effective and valuable in raising diabetic patients' self-confidence and support. It is suggested that healthcare providers and institutions include support group programs in the usual treatment for diabetes patients, as these programs boost patients' confidence in their abilities and lead to better results.